Genetic landscape of hypertrophic cardiomyopathy in Hong Kong Chinese population - Lee, Derek P. H.; Cao, Ye; Zhang, Lilei (Frontiers in Genetics, 2025)
IntroductionAsian populations are underrepresented in the hypertrophic cardiomyopathy (HCM) genomic databases, which are currently largely dominated by Caucasian population. We aim to characterize the genetic landscape of HCM in patients from Hong Kong Chinese population.MethodsFrom March 2023 to March 2024, fifty-three unrelated patients with an unequivocal clinical diagnosis of HCM were enrolled at a single tertiary center in Hong Kong and underwent genetic testing using a standardized 19-gene panel.ResultsIn this cohort study, we identified 13 patients (24.5%) with a predominant pathogenic or likely pathogenic (P/LP) variant and 12 patients (22.6%) with a predominant variant of unknown significance (VUS). Most of the P/LP variants identified were in MYBPC3 (46.2%, n = 6) or MYH7 (38.5%, n = 5). Novel genetic variants were identified in 5 patients. Multiple genetic variants identified in the same patient were common (13.2%, n = 7). All disease-causing variants are rare with allele frequencies <0.00005 in all populations and <0.0002 in East Asian subpopulation. Specifically in this unrelated cohort, we identified several recurrent variants including MYH7:c.1987C>T (p.Arg663Cys) pathogenic missense variant (n = 2), MYBPC3:c.1038_1042dup (p.Met348Thrfs*4) pathogenic truncating variant (n = 3) and MYBPC3:c.1000G>A (p.Glu334Lys) missense VUS (n = 3). Patients with P/LP variants were associated with an increased risk of developing left ventricular dysfunction (p = 0.012).ConclusionOur study provided insight into the genetic landscape of HCM in Hong Kong Chinese population. We identified several recurrent variants and novel variants in our HCM cohort. Patients with P/LP variants were associated with an increased risk of developing left ventricular dysfunction. Future studies on the potential founder effects of these recurrent variants, cumulative effects of multiple variants, and longitudinal follow up of HCM patients would be useful.